PENGARUH KARAKTERISTIK KOMUTER DI KOTA-KOTA SATELIT PADA KAWASAN JABODETABEK - Machmud, Sulthon Kamel; Nouri, Mh Nateq (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Government Regulation No. 13/2017 (RTRWN) establishes the Jabodetabekpunjur metropolitan area as an urban area with a nodal structure consisting of a core and hinterland, which interact with each other in commuter mobility. This study aims to investigate how the characteristics of commuters from satellite cities in the Jabodetabek region affect population movement, with the aim of reducing negative impacts such as congestion and regional inequality. The data collection method is based on the 2019 Jabodetabek Commuter Statistics document, with analysis using the interval/ratio association approach, multiple linear regression, and route selection modeling using the all-or-nothing assignment model in the context of transportation analysis. The results show that the characteristics of the number of commuters in Jabodetabek satellite cities are related to main activities such as work and school but have no effect on commuters heading to Jakarta. The main reasons for commuters to work at their destination are compatibility with education/skills, lack of other alternatives, and high income levels, while the main activity of schooling is related to the quality of education in the origin region. The majority of routes in satellite cities have alternatives except for Bekasi Regency, which only has one route option, with the longest travel time from Tangerang Regency and the fastest from South Tangerang City.